2022
DOI: 10.1039/d1ob02436a
|View full text |Cite
|
Sign up to set email alerts
|

Iodine-catalyzed oxidative annulation: facile synthesis of pyrazolooxepinopyrazolones via methyl azaarene sp3 C–H functionalization

Abstract: An iodine-catalytic methyl azaarenes sp3 C-H functionalization has been developed for synthesis of a seven-membered O-heterocyclic architecture containing three different heterocyclic aromatic hydrocarbons. This method can be applied to a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Seven membered O-heterocycles 52 were found in nature and show several bioactivities like anticancer, anti-mycobacterial and antifungal activities. Zhang and Zhu et al in 2022 reported a multi-component approach for the synthesis of fused seven-membered oxygen heterocycles; pyrazolooxepinopyrazolones 146 were obtained from the reaction of methyl azaarene 20 and dihydropyrazolones 145 in the iodine–DMSO medium (Scheme 35).…”
Section: Kornblum Oxidationmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven membered O-heterocycles 52 were found in nature and show several bioactivities like anticancer, anti-mycobacterial and antifungal activities. Zhang and Zhu et al in 2022 reported a multi-component approach for the synthesis of fused seven-membered oxygen heterocycles; pyrazolooxepinopyrazolones 146 were obtained from the reaction of methyl azaarene 20 and dihydropyrazolones 145 in the iodine–DMSO medium (Scheme 35).…”
Section: Kornblum Oxidationmentioning
confidence: 99%
“…Zhang and Zhu et al in 2022 reported a multi-component approach for the synthesis of fused seven-membered oxygen heterocycles; pyrazolooxepinopyrazolones 146 were obtained from the reaction of methyl azaarene 20 and dihydropyrazolones 145 in the iodine–DMSO medium (Scheme 35). 52 During the optimization study various acid additives such as TfOH, AcOH, HCl, TsOH and TFA were investigated. The best result was obtained in the presence of 2.0 equivalents of TFA.…”
Section: Kornblum Oxidationmentioning
confidence: 99%